Aberrant Promoter Methylation of Protocadherin8 (PCDH8) in Serum is a Potential Prognostic Marker for Low Gleason Score Prostate Cancer - Lin, Ying-Li (Med Sci Monit, 2017)
BACKGROUND: PCDH8 is a newly-discovered suppressor gene that is frequently inactivated by aberrant methylation in several human cancers, including prostate cancer. The identification of PCDH8 methylation can be used as a potential predictive biomarker. Prostate cancer patients with high Gleason score are considered as being at high risk for tumor recurrence and progression, and adjuvant therapy is often routinely performed in clinical practice. In the present study, we did not measure the methylation of PCDH8 in these patients. The main purpose of the present study was to evaluate the clinical significance of PCDH8 methylation in serum of prostate cancer patients with low Gleason score. MATERIAL/METHODS: PCDH8 methylation in serum samples of 117 patients and 47 controls was checked by methylation-specific PCR (MSP). Then, we correlated PCDH8 methylation status with the clinicopathological parameters of prostate cancer patients with low Gleason score and patient outcomes. RESULTS: We found that PCDH8 was more frequently methylated in serum samples of patients with prostate cancer than in controls. PCDH8 methylation was correlated with advanced clinical stage (P=0.021), higher level of preoperative PSA (P=0.008), and positive lymph node metastasis (P=0.010). Moreover, patients with PCDH8 methylation had worse biochemical recurrence (BCR)-free survival (P<0.001) than patients without. Independent prognostic factors for worse BCR-free survival of prostate cancer patients with low Gleason score were: PCDH8 methylation in serum (Exp (B)=3.147, 95% CI: 1.152–7.961, P=0.007), clinical stage (Exp (B)=2.53, 95% CI: 1.032–4.763, P=0.025) and lymph node status (Exp (B)=1.476, 95% CI: 1.107–4.572, P=0.042). CONCLUSIONS: Our study indicated that PCDH8 methylation in serum occurred frequently in prostate cancer patients and was correlated with risk factors for poor outcome. The methylation of PCDH8 in serum is a potential predictive marker for prostate cancer patients with low Gleason score after surgery.